Melatonin Synergizes With Methylprednisolone to Ameliorate Acute Spinal Cord Injury - Bi, Jiaqi; Sun, Peiyu; Feng, Erwei; Shen, Jianxiong; Chen, Chong; Tan, Haining; Li, Zheng; Lin, Youxi (Frontiers in Pharmacology, 2022)
Methylprednisolone (MP) is the drug of choice for treating spinal cord injury (SCI), but the aggressive dosage regimen used often results in adverse side effects. Therefore, MP should be combined with other drugs to lower the required dose. Melatonin is effective in alleviating nerve damage and inhibiting axonal degeneration. The combination of melatonin and half-dose methylprednisolone (HMP) for spinal cord injury treatment has never been reported. In this study, we established a rat model of T9 spinal cord injury by the Allen's method and assessed the synergistic therapeutic effects of melatonin and HMP by factorial design. Our results demonstrated that melatonin could synergize with HMP to ameliorate acute SCI through PI3K-AKT1 pathway. Combining melatonin with HMP significantly reduced the standard-dose of methylprednisolone and limited its adverse reactions, representing a promising option for treating acute SCI.